Reduced Victim Participation: A Misstep by the Extraordinary Chambers in the Courts of Cambodia - David S. Sokol (Washington University Global Studies Law Review, 2011)
The article focuses on the ruling of the Extraordinary Chambers in the Courts of Cambodia (ECCC) which reduces the participation of the victims of the Cambodian conflict in the criminal trial proceedings of their tormentors and former members of the Khmer Rouge. It explores the goals of the ECCC. A brief historical overview of the Khmer Rouge conflict from April 17, 1975 to January 6, 1979, which resulted in the need for an international tribunal, is presented.
Keywords: Victims of terrorism -- Legal status, laws, etc.; Criminal trials; Cambodia -- Politics & government -- 1975-1979; Parti communiste du Kampuchéa